A Simple Probe for the Colorimetric Detection of Carbon Dioxide. Issue 51 (8th November 2013) - Climent, Estela; Agostini, Alessandro; Moragues, María E.; Martínez‐Máñez, Ramón; Sancenón, Félix; Pardo, Teresa; Marcos, M. Dolores
<x xml:space="preserve">Abstract</x> Blue with CO2! A new approach for the chromogenic sensing of carbon dioxide using silica nanoparticles functionalized with amino and thiol moieties has been reported. The presence of CO2 in suspensions of the hybrid silica nanoparticles controlled the access of a squaraine dye to the surface of the nanoparticles resulting in a chromogenic response (see figure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>